An Evaluation of Group Housing Affordability in Core Kolkata: The Case of Low-To-Middle Income Groups - Sen Chatterjee, Runa; Chatterjee, Bani (International Journal of Property Sciences (E-ISSN: 2229-8568), 2013)
The concentration of commercial and economic activities in the urban areas due to the increased pace of urbanization in developing nations, like India, has led to an increased migration to urban areas for livelihood opportunities. This has created severe pressure on urban housing. The demand supply balance is skewed across different price segments with demand outstripping supply in the affordable segment and excess supply in the luxury segment. In this context, the present paper aims to evaluate group housing affordability by low to middle income group of population (also referred to as ‘Aspirers’) in core Kolkata. The analyses have been carried out in three steps. First, the income-expenditure (Y-E), pattern of the target group have been studied to identify their affordability thresholds. Secondly, a relationship between the income expenditure pattern and group housing prices have been established through the affordability indices. Finally, the probability of owning a group housing unit in Kolkata has been evaluated from the probability of house ownership by Asset Holding Classes in urban West Bengal. The paper has established a basis for earmarking long-term policies on fixing the pricing pattern of future group housing ventures in Kolkata best matching the affordability pattern of the low-to-middle income group.